Dental Puzzle-Based Little Dentist Training on Oral Health Promotion among Elementary School Students - Berlian Shinta Faradiansyah; Hayyu Failasufa; Zalfa Alzena; Tegar Pramudita; Inggranita Oktavania Farashanty; Ita Febriani (Journal Center of Excellent : Health Assistive Technology, 2026)
Oral and dental health problems among elementary school children remain prevalent and require innovative promotive–preventive approaches. This study aimed to improve knowledge, attitudes, and behaviors related to oral health through training of Little Dentists using dental puzzle media at SDN Mangkang Kulon 1, Semarang City. A total of 24 sixth-grade students participated on 4–5 August 2025. This study employed a pre-experimental design with a one-group pre-test and post-test approach, and participants were selected using purposive sampling. Methods included interactive education, group discussions, toothbrushing practice, dental puzzle games, and evaluation with pre- and post-test questionnaires. Data were analyzed using a paired t-test. Results showed significant improvements in knowledge (p < 0.001), attitudes (p = 0.001), and behaviors (p = 0.005) after the intervention. Dental puzzle media effectively engaged participants and facilitated active learning. These findings indicate that peer-led Little Dentist training with interactive media is an effective promotive–preventive strategy and has potential for sustainable integration into school-based Dental Health Programs (UKGS).